Effect of Polypropylene Fiber Reinforced on Properties of Concrete - Alsadey, Salahaldein (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2016)
This paper investigates on analyzing the effects of use of Polypropylene fiber in the mechanical properties of concrete. One of the main tasks of the construction industry is to increase the strength and reliability of structures while reducing construction costs. Effective use of fiber reinforced concrete is likely to lead to reduction in reinforcement. Three mixes used polypropylene fiber with content 1.0%, 1.5%, and 2.0% percent. To provide a basis for comparison, reference specimens were cast without polypropylene fiber. The test results showed that the increase of mechanical properties (compressive strength) resulting from added of polypropylene fiber was relatively high.